Problematizing the «mermelada»: State advertising and its influence on the media agenda in Peru - Cordero, Jaime (2024)
This article examines the influence of state advertising on the media in Peru, focusing on the concept of «mermelada», a term used to describe the exchange of economic or advertising favors between the state and the media in return for favorable coverage. Through a review of the literature on media capture and a quantitative analysis of historical data on state advertising investment, the study concludes that, while the narrative of «mermelada» has gained strength in political discourse, the state's actual ability to capture major media outlets is in decline.